2021
DOI: 10.3389/fcimb.2021.706618
|View full text |Cite
|
Sign up to set email alerts
|

Tityus serrulatus (Scorpion): From the Crude Venom to the Construction of Synthetic Peptides and Their Possible Therapeutic Application Against Toxoplasma gondii Infection

Abstract: Toxoplasmosis, caused by Toxoplasma gondii, is a major public concern owing to its neurotropic nature and high morbidity and mortality rates in immunocompromised patients and newborns. Current treatment for this disease is inefficient and produces side effects. Inflammatory mediators produced during T. gondii infection (e.g., cytokines and nitric oxide) are crucial in controlling parasite replication. In this context, Tityus serrulatus venom (TsV) induces the production of inflammatory mediators by immune cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Tityus serrulatus venom (TsV) is a mixture of active components from scorpion with immunomodulatory properties ( de Assis et al, 2021 ). It has been extensively studied for its pro-inflammatory, T-lymphocyte activation which can stimulate the expression of inflammatory factors, such as interleukins, tumor necrosis factor (TNF) and interferon-γ (IFN-γ) ( Zoccal et al, 2011 ; Casella-Martins et al, 2015 ).…”
Section: Animal Venoms and Venom-derived Molecules With Anti- ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Tityus serrulatus venom (TsV) is a mixture of active components from scorpion with immunomodulatory properties ( de Assis et al, 2021 ). It has been extensively studied for its pro-inflammatory, T-lymphocyte activation which can stimulate the expression of inflammatory factors, such as interleukins, tumor necrosis factor (TNF) and interferon-γ (IFN-γ) ( Zoccal et al, 2011 ; Casella-Martins et al, 2015 ).…”
Section: Animal Venoms and Venom-derived Molecules With Anti- ...mentioning
confidence: 99%
“…It has been extensively studied for its pro-inflammatory, T-lymphocyte activation which can stimulate the expression of inflammatory factors, such as interleukins, tumor necrosis factor (TNF) and interferon-γ (IFN-γ) ( Zoccal et al, 2011 ; Casella-Martins et al, 2015 ). De Assis et al (2021) extracted scorpion venom and distilled using chromatography to obtain seven subgroups (F1, F2, F3, F4, F5, F6, and F7). About the anti- T. gondii activity in vitro of these seven subgroups, only F6 and F7 induced nitric oxide (NO) production in macrophages (MOs) at safe concentrations and exerted biological activity.…”
Section: Animal Venoms and Venom-derived Molecules With Anti- ...mentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one study reporting peptide efficacy against T. gondii tissue cysts. The venom of the scorpion Tityus serrulatus was evaluated, and the Pep 1 peptide decreased the number of cerebral tissue cysts in infected mice, although its mechanism of action is still unknown [ 72 , 73 , 74 ].…”
Section: Peptides Active Against Apicomplexan Parasitesmentioning
confidence: 99%
“…It has been recommended that Ts7 fraction from crude TsV contains components that are responsible for generating pro-inflammatory immune responses of T. cruzi -infected macrophages [ 55 ] . It has also been confirmed that TsV components can induce the production of inflammatory mediators by immune cells against Toxoplasma gondii activity [ 56 ] . Mesobuthus eupeus has shown considerable antimicrobial and antiviral activity.…”
Section: Introductionmentioning
confidence: 99%